Beneficial Effect of Short Pretransplant Period of Hypothermic Pulsatile Perfusion of the Warm-Ischemic Kidney after Cold Storage: Experimental Study. (31st July 2016) - Lázaro, Alberto; Humanes, Blanca; Jado, Juan Carlos; Mojena, Marina; González-Nicolás, María Ángeles; del Cañizo, Juan Francisco; Tejedor, Alberto; Lledó-García, Enrique
Abstract : Warm ischemia (WI) produces a significant deleterious effect in potential kidney grafts. Hypothermic machine perfusion (HMP) seems to improve immediate graft function after transplant. Our aim was to analyze the effect of short pretransplant periods of pulsatile HMP on histology and renal injury in warm-ischemic kidneys. Twelve minipigs were used. WI was achieved in the right kidney by applying a vascular clamp for 45 min. After nephrectomy, autotransplant was performed following one of two strategies: cold storage of the kidneys or cold storage combined with perfusion in pulsatile HMP. The graft was removed early to study renal morphology, inflammation (fibrosis), and apoptosis. Proinflammatory activity and fibrosis were less pronounced after cold storage of the kidneys with HMP than after cold storage only. The use of HMP also decreased apoptosis compared with cold storage only. The detrimental effects on cells of an initial and prolonged period of WI seem to improve with a preservation protocol that includes a short period of pulsatile HMP after cold storage and immediately before the transplant, in comparison with cold storage only.